The Global Ecosystem of Academe and Research Cooperation: Risks and Geopolitics - Johnson, Mark (International Higher Education, 2021)
The COVID-19 pandemic has illuminated and exacerbated “pressure cracks” within national higher educational systems, as well as emerging risks in the larger ecosystem of international higher education and research cooperation. These risks of geopolitical conflict and ethnonationalist politics could interact to generate powerful countercurrents to established student and scholar mobility and “knowledge diplomacy.” Such rising barriers could, in turn, close off any meaningful hope of addressing our increasingly disruptive global emergencies.